2008
DOI: 10.1177/039139880803100906
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectric Effect and Bacterial Biofilms. a Systematic Review

Abstract: Bacteria growing in biofilms cause a wide range of human infections. Biofilm bacteria are resistant to antimicrobics at levels 500 to 5,000 times higher than those needed to kill non-biofilm bacteria. In vitro experiments have shown that electric current can enhance the activity of some antimicrobial agents against certain bacteria in biofilms; this has been termed the “bioelectric effect”. Direct electrical current has already been safely used in humans for fracture healing. Application of direct electric cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 42 publications
(77 reference statements)
2
100
0
2
Order By: Relevance
“…This would be a potential strategy for overcoming the reduced susceptibility of biofilm microorganisms to conventional antimicrobial agents. The mechanism of the antibacterial activity of electrical current is unknown; however, this activity has been suggested to result from toxic substances produced as a result of electrolysis (e.g., H 2 O 2 , oxidizing radicals, and chlorine molecules) (10,18), oxidation of enzymes and coenzymes, membrane damage leading to leakage of essential cytoplasmic constituents (15), and/or altered bacterial respiratory rate (6). In one study (13), an ionic strength-dependent transfer of electrons during the initial bacterial adhesion mechanism that had to be reversed in order for detachment to occur was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…This would be a potential strategy for overcoming the reduced susceptibility of biofilm microorganisms to conventional antimicrobial agents. The mechanism of the antibacterial activity of electrical current is unknown; however, this activity has been suggested to result from toxic substances produced as a result of electrolysis (e.g., H 2 O 2 , oxidizing radicals, and chlorine molecules) (10,18), oxidation of enzymes and coenzymes, membrane damage leading to leakage of essential cytoplasmic constituents (15), and/or altered bacterial respiratory rate (6). In one study (13), an ionic strength-dependent transfer of electrons during the initial bacterial adhesion mechanism that had to be reversed in order for detachment to occur was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that whilst an electric current enhances the efficacy of the antimicrobial treatment of biofilms, the same electric current without an antimicrobial agent has no significant impact on the numbers of viable biofilm bacteria. However, in the last few years, studies of the long-term exposure of biofilms to a low intensity electrical current have shown that prolonged exposure in the absence of antimicrobial agents resulted in a marked decrease in the viability of a number of biofilm strains [4]. This recent development, known as the electricidal effect, goes contrary to the findings of many previous reports which stated that electric current alone is not effective in killing biofilm bacteria and provides fresh incentive to explore the possibility of designing a new generation of antimicrobial surfaces and devices.…”
Section: Electrical Methods Of Controlling Bacteriamentioning
confidence: 99%
“…It is estimated that they are responsible for 65% of all human microbial infections [1][2][3][4] with treatment costs in excess of one billion dollars per year in the USA [5,6]. The key pathogens responsible for device-related infections are…”
Section: The Problem With Biofilmsmentioning
confidence: 99%
See 2 more Smart Citations